Biodiversity and oenological attitude of Saccharomyces cerevisiae strains isolated in the Montalcino district: biodiversity of S. cerevisiae strains of Montalcino wines. Issue 2 (29th January 2021) - Guzzon, Raffaele; Roman, Tomas; Larcher, Roberto; Francesca, Nicola; Guarcello, Rosa; Moschetti, Giancarlo
ABSTRACT: The biodiversity of Saccharomyces cerevisiae was studied in the Montalcino area (Italy). Two wineries were involved in the study, which compared the genotypic and oenological characteristics of the S. cerevisiae strains isolated in spontaneous fermentations. After isolation yeasts were identified by 26S rRNA gene sequence analysis, and S. cerevisiae strains were characterized through interdelta sequence analysis (ISA). Oenological tests were performed in synthetic grape must by varying the magnitude of the main wine-imiting factors. The evolution of alcoholic fermentation was monitored by measuring sugar consumption and flow cytometry. The results revealed the prevalence of S. cerevisiae from the third day of fermentation and the presence of a wide range of S. cerevisiae strains having ISA profiles characteristic of each winery. From an oenological point of view, the features of such strains, in terms of resistance to wine-limiting factors, seemed to be linked to the main oenological variables applied in the production process of each winery. Extreme fermentation temperatures and copper residues are the variables that mostly depress the yeast population, in terms of fermentation rate and cell viability. Flow cytometry revealed the different impact of limiting factors on the viability of yeast by the quantification of the ratio between live/dead yeast cells of each strain, suggesting different mechanisms of inhibition, for instance stuck of cell growth or cell killing, in response to the different stress factors. Abstract : This study describes the biodiversity of S. cerevisiae strains in spontaneous fermentation as well as the role of wine making variables and geographical origin of grapes.